Role of the organ of vision in the course of developmental dyslexia - Czepita, Damian; Łodygowska, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: To present and describe the role of the organ of vision in the course of developmental dyslexia. Material and methods: A comprehensive review of contemporary literature about the etiopathogenesis and the clinical symptoms of dyslexia was conducted. Results: Developmental dyslexia in other words is the specific difficulty of a person with reading and writing caused by a deficit in the development of perceptive and motoric functions as well as the coordination of these functions. The etiopathogenesis of dyslexia is not definitely determined. Currently developmental dyslexia is thought to be determined by environmental and genetic factors. In accessible literature it is noted that a total of 5-17.5% of all people is effected by dyslexia. It is widely regarded that 63% of all sufferers of dyslexia develop the auditory type of dyslexia with an additional 9% having the visual type of dyslexia, while the rest develop a mixed type. The basis of visual dyslexia lies in the disorder of visual perception linked to the disorders of visual and motoric coordination as well as visual and spatial integration. People with developmental dyslexia tend to evolve numerous changes in the magnocellular pathway, eyeball movements, accommodation as well as binocular vision.